Development and Characterization of a Mouse Model Overexpressing a Farnesoid-X-Receptor Transgene with Reduced Markers of Intestinal Inflammation (P08-122-19). (24th October 2019) - Wren, Spencer; Donovan, Micah; Selmin, Ornella; Doetschman, Tom; Romagnolo, Donato
Abstract: Objectives: The farnesoid-X-receptor (FXR) regulates bile acid (BA) homeostasis, protecting against colonic inflammation and cancer. Conversely, increased intestinal levels of BA and expression of cyclooxygenase-2 (COX-2) increase the risk of inflammation and cancer of the colon. Earlier studies from our laboratory show that a diet rich in n -6 linoleic acid ( n -6HFD) epigenetically activates Fxr, inducing the expression of downstream factors that regulate BA homeostasis. However, the chronic exposure to n -6HFD induces COX-2 expression through CpG demethylation of the PTSG-2 gene and activates the β-catenin pathway. The objective of this study is to determine in a mouse and cell culture models the influence of an n -6HFD on endpoints of intestinal inflammation and the modifying effects of overexpression of FXR . Methods: A mouse line overexpressing FXR in the intestine was developed by injecting an FXR transgene ( Fxr TG ) construct driven by the villin promoter into FVB zygotes, and then crossed with C57BL6 mice. The small intestine and colon tissue were collected from male founders. Changes in gene expression and DNA methylation were measured by real-time PCR (RT-PCR). Cell culture experiments were performed in colonic human fetal cell (FHC) cells treated with linoleic acid (LA). Results: Expression analyses by RT-PCR reveal increased expression of Fxr TG in distal small intestine and proximal and distal colon. These changes are paralleled by accumulation of ileal bile acid-binding protein (IBABP) and small heterodimer partner (SHP), two downstream targets of FXR, and a reduction in expression of COX-2. Western blot of colon FHC shows LA induces expression of COX-2. Conclusions: We conclude that increased expression of FXR triggers the expression of genes involved in BA homeostasis and downregulates genes involved in inflammation. The Fxr TG mouse model is being used to investigate the modifying effects of diets varying in fatty acid level and profile on endpoints of intestinal inflammation and cancer. Funding Sources: This work was supported by a grant from NIFA, GRANT12445471, and a predoctoral training grant to M.G.D. from the Cancer Biology Training Grant T32CA009213.